The Development of Inheritance Customary Law For The Heirs of Girls According To The Patrilineal Kinship System - Afnaini (Britain International for Academic Research (BIAR) Publisher, 2022)
Inheritance law in Indonesia is still plural, this happens because Indonesia does not yet have a National Inheritance Law that applies to all Indonesian people. In connection with the absence of the law, in Indonesia there are still three (3) kinship systems, i.e. the kinship system, the parental kinship system and the matrilineal kinship system. Additionally, through the Decree of the Supreme Court of the Republic of Indonesia dated November 1, 1961 Reg No. 179/K/Sip/1961 which states that the girl and boy of a joint heir are entitled to inheritance in the sense that the share of boys is equal to that of girls. The problems in this research are 1) how to development of inheritance distribution practices for inheritance to girls in the patrilineal kinship system 2) how is the direction of development of customary inheritance law towards inheritance to girls in the patrilineal kinship system? This study uses research methods with a normative approach. The results showed that the practice of dividing inheritance for inheritance to girls in the patrilineal kinship system has undergone changes in several factors that effect the development of changes in indigenous peoples, including education, overseas/migration, economic and religious factors as well as social court decisions. 2) The direction of development of customary inheritance law towards inheritance to girls in the patrilineal kinship system began with the issuance of Supreme Court Decision Number 179K/Sip/1961 and has moved towards a patrilineal system that provides equality towards equality and rights for boys and girls because it is influenced by human factors, justice and equality between men and women.